ANALISA PENGARUH FAKTOR PENDAPATAN PERKAPITA HARGA KENDARAAN BERMOTOR DAN JUMLAH PENDUDUK MEMPENGARUHI PERMINTAAN KENDARAAN BERMOTOR KOTA SURABAYA - Prayitno, Budi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2007)
The problem in this research is wheather location factor with indicator is distance between and access,price with indicator is prices and discount, product with indicator is variety and mark, inventory and deversification, facility with indicator is shopping room, lay out, and parking room, service with indicator is convidential, capability and safety influece the buy decision for dress in Vida Swalayan at Surabaya. The method use in this research is explanatory research, for making empiric generalization, to determine concept, to prove in developing theory where data collection and analisys go at the same time. The research population are the customers, with 100 samples wich taken in random sampless,where the datas collected were from primary datas with a spread questionary and direct interviews with the respondents and the secondair datas which have been collected from asociated institution. Variables which have observed carefully in this research is the amaunt of goods and expenses as a variable dependent and location,price,productfacility and service as an independent variable. Datas collection were done by direct interviews with the respondent and a direct questionary to consumers in Vida Swalayan. Analisis method with cross tabulation,to sen contingency table wich shows wether there is any collection between dependent variable which cover the amount ofgoods and expenses with and independent variable is location,price,productfacility and service.And chi square tess metode the different between observation and expectation frequency. From the evaluation towards the coeficient chi square calculation result,either from person chi square it will obtain chi square value bigger than chi square table, which means that each variable presence has an significant influence towards consumer purchasing decision. As a whole the dominant influence factor towards the buy decision is amount of goods and expenses.